Preparation method and application of novel metal-organic framework structure composite material based on fly ash and steel slag

By optimizing the treatment methods of fly ash and steel slag, a new efficient metal-organic frame structure composite material PVA-Fe3O4@Al-MOF was prepared, which solved the problems of low metal efficiency and insufficient MOF performance in the existing technology, and achieved a more efficient environmental restoration effect.

CN119657229APending Publication Date: 2025-03-21JIANGSU ZHONGYI ECOLOGICAL SOIL INST +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411839100.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In the prior art, solid waste extraction efficiency is low, and the catalytic and adsorption properties of MOF are insufficient, which affects the environmental restoration efficiency.

Method used

The new metal-organic frame structure composite material PVA-Fe3O4@Al-MOF was prepared by hydrothermal method. By optimizing the extraction of aluminum chloride in fly ash and the preparation of nano-scale Fe3O4 in steel slag, the catalytic characteristics and MOF adsorption properties of the composite material were improved.

Benefits of technology

It significantly improves the catalytic performance of composite materials and the adsorption performance of MOF, enhances the repair ability of petroleum hydrocarbon contaminated soil, and improves the environmental restoration efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657229A_ABST
    Figure CN119657229A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a novel metal-organic framework structure composite material based on fly ash and steel slag, and belongs to the technical field of environmental geotechnical .The preparation method comprises the following steps that aluminum chloride is prepared from fly ash, nanoscale Fe3O4 is prepared from steel slag, and the novel metal-organic framework structure composite material PVA-Fe3O4-Al-MOF is synthesized, the preparation method comprises the following steps: dispersing aluminum chloride into dimethylformamide, and then adding nanoscale Fe3O4 to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution; the preparation method comprises the following steps: dissolving trimesic acid in dimethylformamide to obtain a trimesic acid-dimethylformamide solution; putting the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution into a reaction kettle, heating to react for a period of time, and then carrying out solid-liquid separation to obtain Fe3O4 (at) Al-MOF; adding the Fe3O4 (at) Al-MOF into an aqueous solution of polyvinyl alcohol, soaking for a period of time, and then filtering to obtain PVA-Fe3O4 (at) Al-MOF;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental geotechnical technology, and specifically relates to a preparation method of a novel metal-organic framework composite material based on fly ash and steel slag and application thereof. Background Art

[0002] Fly ash, commonly known as fly ash, refers to the fine ash collected from the flue gas after coal combustion. It is the main solid waste discharged by coal-fired power plants. Fly ash is usually gray or gray-black. The main oxide components of fly ash are SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. Steel slag mainly comes from the oxides formed by the oxidation of elements contained in molten iron and scrap steel, impurities brought in by metal charge, slag-making agents such as limestone, fluorite, silica, etc., as well as oxidants, desulfurization products and corroded furnace lining materials; the main components of steel slag are calcium, iron, silicon, magnesium, aluminum, manganese, phosphorus and other oxides. As an important component of industrial waste, the effective use of fly ash and steel slag can not only reduce the pressure of solid waste treatment, but also provide new materials and methods for environmental remediation. Based on this, domestic and foreign researchers have gradually turned their attention to the use of these wastes to synthesize new materials and apply them to the research of environmental remediation technology.

[0003] In terms of the current international research status, research on the synthesis of functional materials using industrial solid waste such as fly ash and steel slag has made certain progress. For example, some researchers extracted aluminum from fly ash by chemical methods and used it to synthesize aluminum-based metal-organic frameworks (Al-MOF). At the same time, the use of steel slag to prepare different forms of iron oxides (such as Fe3O4) has also become a research hotspot. Fe3O4 has excellent magnetic and catalytic properties and is widely used in environmental remediation. Loading Fe3O4 on Al-MOF can form a new composite material Fe3O4@Al-MOF. This composite material only uses the high specific surface area of ​​MOF to adsorb Fe3O4 to produce catalytic properties. After Fe3O4 leaves MOF, MOF further adsorbs pollutants and is not further developed and utilized.

[0004] Domestic research is also advancing rapidly. Researchers have proposed several innovative synthesis methods and application solutions for the comprehensive utilization of fly ash and steel slag. Specifically, the extraction of aluminum from fly ash and the synthesis of aluminum-based MOF by hydrothermal method has been proven to be an efficient preparation method. At the same time, researchers also used steel slag to prepare high-purity Fe3O4 and loaded it on the synthesized Al-MOF to successfully construct Fe3O4@Al-MOF composite materials. This composite material has shown great application potential in the field of catalysis, especially in the remediation of contaminated soil.

[0005] Although research in this field at home and abroad has achieved certain results, there are still some technical difficulties that need to be solved. First, how to improve the efficiency of extracting aluminum from fly ash and ensure the economy and environmental protection of the extraction process is an important research direction. Secondly, during the synthesis of Fe3O4@Al-MOF, how to ensure the uniform distribution of Fe3O4 in Al-MOF and control its particle size and morphology to ensure its optimal catalytic performance is another technical bottleneck that needs to be broken through. Finally, in addition to the catalytic performance of this composite material in actual environmental remediation, how to further utilize the high specific surface area of ​​MOF to adsorb pollutants is also a key factor affecting the improvement of remediation efficiency. Summary of the invention

[0006] Purpose of the invention: In view of the low purity of the materials obtained by extracting metals from existing solid wastes and synthesizing metal-organic framework structures, and the weak adsorption and catalytic ability of MOF after synthesis, the present invention provides a method for preparing a new metal-organic framework composite material based on fly ash and steel slag. The preparation method uses fly ash and steel slag to prepare a new metal-organic framework composite material PVA-Fe3O4@Al-MOF by a hydrothermal method, optimizes the method of preparing aluminum chloride from fly ash and extracting nano-Fe3O4 from steel slag, and improves the catalytic properties of the composite material and the adsorption performance of MOF by controlling the synthesis conditions. The present invention also provides a method for repairing petroleum hydrocarbon contaminated soil using a new metal-organic framework composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate.

[0007] Technical solution: A method for preparing a novel metal-organic framework composite material based on fly ash and steel slag, comprising the following steps:

[0008] S1. Preparation of aluminum chloride using fly ash: adding fly ash into concentrated hydrochloric acid, mixing and heating to obtain aluminum acid solution, then diluting and filtering to obtain filtrate, cooling the filtrate to room temperature, and precipitating white aluminum chloride crystals;

[0009] S2. Preparation of nano-sized Fe3O4 using steel slag: Put the steel slag into dilute hydrochloric acid, mix and stir for a period of time, and then perform solid-liquid separation to obtain an iron-containing filtrate; add sodium hydroxide to the iron-containing filtrate to obtain an iron hydroxide precipitate; first pyrolyze the iron hydroxide precipitate in an air environment, then pyrolyze it in a hydrogen atmosphere, and finally grind the product to obtain nano-sized Fe3O4;

[0010] S3. Synthesis of a novel metal-organic framework composite material PVA-Fe3O4@Al-MOF: disperse aluminum chloride in dimethylformamide, then add nanometer-sized Fe3O4 to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution; dissolve trimesic acid in dimethylformamide to obtain trimesic acid-dimethylformamide solution; place the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and trimesic acid-dimethylformamide solution in a reactor, heat the reaction for a period of time, and then perform solid-liquid separation to obtain Fe3O4@Al-MOF; add Fe3O4@Al-MOF into an aqueous solution of polyvinyl alcohol, soak for a period of time, and then filter to obtain PVA-Fe3O4@Al-MOF.

[0011] Furthermore, in S1, the volume ratio of fly ash mass to concentrated hydrochloric acid is 1 g: (3-5) ml, and the mass percentage concentration range of concentrated hydrochloric acid is 36%-38%.

[0012] Furthermore, in S2, the volume ratio of steel slag to dilute hydrochloric acid is 1g:(6-10)ml, and the mass percentage concentration of dilute hydrochloric acid is 8%-12%; the temperature of pyrolysis of iron hydroxide precipitate in air environment is 700℃-800℃; the temperature of pyrolysis in hydrogen atmosphere is 900℃-1000℃.

[0013] Furthermore, in S2:

[0014] 1) In the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution, the mass ratio of aluminum chloride to dimethylformamide is (0.534-0.801) g:1 L, and the mass ratio of aluminum chloride to ferroferric oxide is (4.005-5.34):1;

[0015] 2) In the trimesic acid-dimethylformamide solution, the mass ratio of trimesic acid to dimethylformamide is (0.315-0.63) g:1L;

[0016] 3) After the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are mixed, the mass ratio of trimesic acid to aluminum chloride is (3.15-4.725):2.67.

[0017] Furthermore, the specific steps of S1 are as follows:

[0018] S1-1, adding fly ash into concentrated hydrochloric acid, heating the mixed solution at 200°C-300°C for 4h-6h to obtain an aluminum acid solution;

[0019] S1-2, dilute the aluminum acid solution with water to reduce the concentration of aluminum waste liquid, which can improve the filtration speed and efficiency; stir at 80℃-90℃ for 30min-40min, then maintain the temperature and perform hot filtration under stirring; the volume of water added is three to four times the amount of concentrated hydrochloric acid in S1-1;

[0020] S1-3, stirring the liquid obtained after hot filtration at 110°C-120°C for 15min-20min to dissolve more aluminum compounds into the liquid, thereby increasing the aluminum concentration in the aluminum-containing solution; cooling to room temperature to obtain the first precipitation of aluminum chloride white crystals, and performing solid-liquid separation; the remaining filtrate is allowed to stand at room temperature for 12h, and aluminum chloride is precipitated as aluminum chloride white crystals for the second time;

[0021] S1-4, drying the first and second precipitated aluminum chloride white crystals at 70°C-80°C for 12h-14h.

[0022] Furthermore, the specific steps of S2 are as follows:

[0023] S2-1, adding steel slag into dilute hydrochloric acid, mixing and stirring for 12-14 hours, separating the solution into solid and liquid, and obtaining an iron-containing filtrate;

[0024] S2-2, adding sodium hydroxide to the iron-containing filtrate, adjusting the pH to 9-10, obtaining iron hydroxide precipitate, and performing solid-liquid separation when the precipitate no longer continues to be generated;

[0025] S2-3, washing the precipitate with deionized water, and then pyrolyzing the precipitate in an air atmosphere for 8h-10h;

[0026] S2-4, then taking out the solid matter and pyrolyzing it in a hydrogen atmosphere for 4h-6h;

[0027] S2-5. Grind the obtained product using a grinding device to obtain nano-sized Fe3O4.

[0028] The specific steps of S3 are as follows:

[0029] S3-1, dispersing aluminum chloride in dimethylformamide, adding nano-sized Fe3O4 thereto, and ultrasonically treating for 30 min-60 min to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution; dissolving trimesic acid in dimethylformamide, and ultrasonically treating for 30 min-60 min to obtain a trimesic acid-dimethylformamide solution;

[0030] S3-2, placing the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution in a reaction kettle, and heating them in a hot environment of 120° C.-140° C. for 8 h-10 h to obtain a solid-liquid mixed solution;

[0031] S3-3, cooling the solid-liquid mixed solution to room temperature, performing solid-liquid separation, and obtaining Fe3O4@Al-MOF in a wet state;

[0032] S3-4. Use dimethylformamide to clean Fe3O4@Al-MOF and dry it in a hot environment of 60℃-70℃ for 12h.

[0033] S3-5, dissolving polyvinyl alcohol (PVA) powder in water to prepare a polyvinyl alcohol solution with a mass percentage concentration of 5%-6%, and letting it stand to room temperature (25°C);

[0034] S3-6, adding Fe3O4@Al-MOF to the PVA solution, ensuring that the Fe3O4@Al-MOF material is completely immersed and fully stirred for 30min-60min, soaking for 5 to 6 days, and filtering to obtain PVA-Fe3O4@Al-MOF;

[0035] Step S3-7, the PVA-Fe3O4@Al-MOF was rinsed alternately with water and ethanol, and then dried in a hot environment of 60°C-70°C for 12h.

[0036] The present invention provides a method for repairing petroleum hydrocarbon contaminated soil by catalyzing sodium percarbonate using a novel metal-organic framework structure composite material (PVA-Fe3O4@Al-MOF), comprising the following steps:

[0037] Step 1: Pre-treating the petroleum hydrocarbon contaminated soil;

[0038] Step 2: Preparation of repair agent using PVA-Fe3O4@Al-MOF

[0039] Sodium percarbonate was dispersed in water to obtain solution A; PVA-Fe3O4@Al-MOF was dispersed in water and citric acid was added to obtain solution B;

[0040] In solution A, the mass ratio of sodium percarbonate to water is 1:7;

[0041] In solution B, the mass ratio of PVA-Fe3O4@Al-MOF to water was 1:3, and the mass ratio of citric acid to PVA-Fe3O4@Al-MOF was 2:1;

[0042] Step 2: Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly, then pour solution A into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes;

[0043] In petroleum hydrocarbon contaminated soil, the dosage of sodium percarbonate, PVA-Fe3O4@Al-MOF, and citric acid is 3%-8%, and the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 2:(1-4);

[0044] Step 3: Let the soil stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0045] Furthermore, the pretreatment method for petroleum hydrocarbon contaminated soil is: air-drying the soil, removing stones and roots, and passing through a 2 mm sieve.

[0046] Beneficial effects:

[0047] 1) The present invention effectively utilizes industrial solid waste fly ash and steel slag to prepare a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF, thereby reducing the damage of pollutants to the environment.

[0048] 2) The present invention optimizes the method of extracting aluminum from fly ash to prepare aluminum chloride and the method of extracting and preparing nano-Fe3O4 using steel slag, adopts multiple evaporation methods to improve the recovery efficiency of aluminum elements, and controls the particle size of Fe3O4 by grinding, which can increase the specific surface area of ​​Fe3O4 and thus improve the loading success rate and quantity in Al-MOF, thereby better catalyzing sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0049] 3) The present invention improves the catalytic properties of the composite material and the adsorption performance of MOF by controlling the synthesis conditions. Compared with the simple method of only mixing the carried material with the carrier in the traditional MOF synthesis process, the present invention adds polyvinyl alcohol as an adhesive to help connect metal ions and organic ligands, enhance the structural stability of the material, and help form a stable three-dimensional network structure. It can also help to evenly disperse metal precursors and organic ligands, reduce particle agglomeration, and thus obtain more uniform MOF nanoparticles or microspheres, so as to better achieve the catalytic effect to repair environmentally polluted media.

[0050] 4) The present invention also provides a method for repairing petroleum hydrocarbon contaminated soil by catalyzing sodium percarbonate using a novel metal-organic framework composite material PVA-Fe3O4@Al-MOF. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a flow chart of the preparation method and application method of the present invention;

[0052] Figure 2 This is a schematic diagram showing the effect of the amount of concentrated hydrochloric acid used in the preparation of aluminum chloride on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0053] Figure 3This is a schematic diagram showing the effect of the amount of dilute hydrochloric acid used in the preparation of Fe3O4 on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0054] Figure 4 Schematic diagram of the effect of temperature on the catalytic performance of PVA-Fe3O4@Al-MOF during the pyrolysis of iron hydroxide precipitation;

[0055] Figure 5 Temperature in the process of hydrogen reduction of iron hydroxide precipitation pyrolysis products

[0056] Schematic diagram of the impact results on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0057] Figure 6 Schematic diagram of the effect of aluminum chloride content on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0058] Figure 7 Schematic diagram of the effect of Fe3O4 content on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0059] Figure 8 Schematic diagram of the effect of trimesic acid content on the catalytic performance of PVA-Fe3O4@Al-MOF;

[0060] Fig. 9 This is a schematic diagram showing the effect of the dosage of the reagent on the remediation efficiency of petroleum hydrocarbon contaminated soil;

[0061] Fig.10 Schematic diagram of the effects of sodium percarbonate and PVA-Fe3O4@Al-MOF dosage on the remediation efficiency of petroleum hydrocarbon contaminated soil. DETAILED DESCRIPTION

[0062] The technical solution of the present invention is described in detail below through embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0063] In the following examples, the fly ash comes from a power plant and the steel slag comes from a metal product processing company. In the following examples, the calculation method of the repair efficiency is:

[0064]

[0065] Example 1

[0066] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0067] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0068] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0069] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g: ml) is 1:4, the dilute hydrochloric acid concentration is 10%, mix and stir for 12 hours, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is first pyrolyzed in an air atmosphere for 8 hours at a temperature of 600°C. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4 hours at a temperature of 800°C. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0070] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0071] Aluminum chloride was dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide (g:L) was 0.267:1. Nano-sized Fe3O4 was added thereto, and the mass ratio of aluminum chloride to Fe3O4 was 2.67:1. Ultrasonic treatment was performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid was taken, and the mass ratio of trimesic acid to aluminum chloride was 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide (g:L) was 0.63:1. Ultrasonic treatment was performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution were placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Use dimethylformamide to clean Fe3O4@Al-MOF and dry it in a hot environment at 60℃ for 12h. Take polyvinyl alcohol powder and dissolve it in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and let it stand to room temperature (25℃). Add Fe3O4@Al-MOF to the PVA solution, ensure that the MOF material is completely immersed and stir well for 30 minutes, and soak for 5 days. Filter the treated PVA-Fe3O4@Al-MOF and rinse it alternately with water and ethanol. Then, dry it in a hot environment at 60℃ for 12h.

[0072] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0073] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the petroleum hydrocarbon concentration in the soil. And calculate the remediation efficiency of petroleum hydrocarbon contaminated soil.

[0074] Example 2

[0075] The volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) was changed to 1:3, and the addition amounts of other components and the operation were the same as in Example 1.

[0076] Example 3

[0077] The volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) was changed to 1:4, and the addition amounts of other components and the operation were the same as in Example 1.

[0078] Example 4

[0079] The volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) was changed to 1:5, and the addition amounts of other components and the operation were the same as in Example 1.

[0080] Examples 1 to 4 investigated the effect of the amount of concentrated hydrochloric acid used in the preparation of aluminum chloride on the catalytic performance of PVA-Fe3O4@Al-MOF. Figure 2 As shown, when the fly ash mass to concentrated hydrochloric acid volume ratio (g:ml) is 1:(3-5), the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%.

[0081] Example 5

[0082] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0083] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:4. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0084] 2) Extract iron from steel slag and prepare Fe3O at nanoscale 4。

[0085] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:6, and the concentration of dilute hydrochloric acid is 10%. Mix and stir for 12 hours, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is first pyrolyzed in an air atmosphere for 8 hours at a temperature of 600°C. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4 hours at a temperature of 800°C. Use grinding equipment to grind the resulting product to obtain nano-grade Fe3O4.

[0086] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0087] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0088] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0089] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0090] Example 6

[0091] The volume ratio (g:ml) of steel slag mass to dilute hydrochloric acid was changed to 1:8, and the addition amounts of other components and the operation were the same as in Example 5.

[0092] Example 7

[0093] The volume ratio (g:ml) of steel slag mass to dilute hydrochloric acid was changed to 1:10, and the addition amounts of other components and the operation were the same as in Example 5.

[0094] Examples 5 to 7 investigated the effect of the amount of dilute hydrochloric acid used in the preparation of nano-sized Fe3O4 from steel slag for iron extraction on the catalytic performance of PVA-Fe3O4@Al-MOF. Figure 3 As shown, when the volume ratio of steel slag to dilute hydrochloric acid (g:ml) is 1:(6-10), the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%. And when it is 1:(8-10), it exceeds 56%.

[0095] Example 8

[0096] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0097] Put fly ash into concentrated hydrochloric acid, the fly ash mass and concentrated hydrochloric acid volume ratio (g:ml) is 1:2, and the concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0098] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0099] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12h, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is first pyrolyzed in an air atmosphere for 8h at a temperature of 400℃. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4h at a temperature of 800℃. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0100] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0101] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0102] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0103] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0104] Example 9

[0105] The temperature during the pyrolysis of the iron hydroxide precipitate was changed to 500° C., and the addition amounts of other components and the operation were the same as in Example 8.

[0106] Example 10

[0107] The temperature during the pyrolysis of the iron hydroxide precipitate was changed to 700° C., and the addition amounts of other components and the operation were the same as in Example 8.

[0108] Embodiment 11

[0109] The temperature during the pyrolysis of the iron hydroxide precipitate was changed to 800° C., and the addition amounts of other components and the operation were the same as in Example 8.

[0110] Examples 8 to 11 investigated the effect of temperature on the catalytic performance of PVA-Fe3O4@Al-MOF during the pyrolysis of iron hydroxide precipitation in air atmosphere. Figure 4 As shown, when the temperature during the pyrolysis of iron hydroxide precipitation is 700°C-800°C, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 60%.

[0111] Example 12

[0112] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0113] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0114] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0115] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the dilute hydrochloric acid concentration is 10%, mix and stir for 12 hours, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is first pyrolyzed in an air atmosphere for 8 hours at a temperature of 600°C. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4 hours at a temperature of 600°C. Use grinding equipment to grind the resulting product to obtain nano-grade Fe3O4.

[0116] 3) Synthesis of a new metal-organic framework composite material PVA-Fe3O4@Al-MOF

[0117] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0118] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0119] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0120] Embodiment 13

[0121] The temperature during the process of reducing the pyrolysis product of iron hydroxide precipitation with hydrogen changes to 700° C., and the addition amounts of other components and the operation are the same as in Example 12.

[0122] Embodiment 14

[0123] The temperature during the process of reducing the pyrolysis product of iron hydroxide precipitation with hydrogen changes to 900° C., and the addition amounts of other components and the operation are the same as in Example 12.

[0124] Embodiment 15

[0125] Only the temperature change during the process of reducing the pyrolysis product of iron hydroxide precipitation with hydrogen was 1000° C. The addition amounts of other components and the operation were the same as in Example 12.

[0126] Examples 12 to 15 investigated the effect of temperature on the catalytic performance of PVA-Fe3O4@Al-MOF during the process of hydrogen reduction of pyrolysis products of iron hydroxide precipitation. The results are as follows: Figure 5 As shown, when the temperature is between 900°C and 1000°C, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 60%.

[0127] Example 16

[0128] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0129] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0130] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0131] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12h, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is first pyrolyzed in an air atmosphere for 8h at a temperature of 600℃. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4h at a temperature of 800℃. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0132] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0133] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.1335:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment at 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0134] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0135] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0136] Embodiment 17

[0137] During the preparation of the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution, the mass ratio of aluminum chloride to dimethylformamide (g:L) was changed to 0.534:1, and the addition amounts of other components and the operations were the same as in Example 16.

[0138] Embodiment 18

[0139] During the preparation of the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution, the mass ratio of aluminum chloride to dimethylformamide (g:L) was changed to 0.801:1, and the addition amounts of other components and the operations were the same as in Example 16.

[0140] Examples 16 to 18 investigated the effect of aluminum chloride content on the catalytic performance of PVA-Fe3O4@Al-MOF during the preparation of aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Figure 6 As shown, when the mass ratio of aluminum chloride to dimethylformamide (g:L) is (0.534-0.801):1, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%.

[0141] Embodiment 19

[0142] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0143] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0144] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0145] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12h, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is pyrolyzed in an air atmosphere for 8h at a temperature of 600℃. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4h at a temperature of 800℃. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0146] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0147] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 1.335:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0148] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0149] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0150] Embodiment 20

[0151] The mass ratio of aluminum chloride to ferrosoferric oxide was changed to 4.005:1, and the addition amounts of other components and the operations were the same as in Example 19.

[0152] Embodiment 21

[0153] The mass ratio of aluminum chloride to ferrosoferric oxide was changed to 5.34:1. The addition amounts of other components and the operation were the same as those in Example 19.

[0154] Examples 19 to 21 investigated the effect of Fe3O4 content on the catalytic performance of PVA-Fe3O4@Al-MOF. Figure 7 As shown, when the mass ratio of aluminum chloride to ferrosoferric oxide is (4.005-5.34):1, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%.

[0155] Embodiment 22

[0156] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0157] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0158] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0159] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g: ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12 hours, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is pyrolyzed in an air atmosphere for 8 hours at a temperature of 600°C. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4 hours at a temperature of 800°C. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0160] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0161] Aluminum chloride was dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide (g:L) was 0.267:1. Nano-sized Fe3O4 was added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) was 2.67:1. Ultrasonic treatment was performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution.

[0162] Take trimesic acid, the mass ratio of trimesic acid to aluminum chloride is 1.575:2.67, dissolve it in dimethylformamide, the mass ratio of trimesic acid to dimethylformamide (g:L) is 0.63:1, and ultrasonically treat it for 30 minutes to obtain a trimesic acid-dimethylformamide solution.

[0163] The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution were placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment of 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution to ensure that the MOF material was completely immersed and stirred for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment of 60°C for 12 hours.

[0164] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0165] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0166] Embodiment 23

[0167] The mass ratio of trimesic acid to aluminum chloride is 3.15:2.67, and the addition amounts of other components and the operations are the same as in Example 22.

[0168] Embodiment 24

[0169] The mass ratio of trimesic acid to aluminum chloride is 4.725:2.67, and the addition amounts of other components and the operation are the same as in Example 12.

[0170] Examples 22 to 24 investigated the effect of trimesic acid content on the catalytic performance of PVA-Fe3O4@Al-MOF. Figure 8 As shown, when the mass ratio of trimesic acid to aluminum chloride is (3.15-4.725):2.67, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%.

[0171] Embodiment 25

[0172] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0173] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%, and the mixed solution is heated at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir it at 85℃ for 30min, and then perform hot filtration. After hot filtration, the liquid is stirred at 115℃ for 15min, cooled to room temperature, and the first precipitated aluminum chloride white crystals are obtained for solid-liquid separation. The obtained solid is dried at 70℃ for 12h, and the remaining filtrate is left to stand at room temperature for 12h, and aluminum chloride is precipitated for the second time. The solid obtained by the second precipitation is dried at 70℃ for 12h.

[0174] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0175] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12h, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is pyrolyzed in an air atmosphere for 8h at a temperature of 600℃. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4h at a temperature of 800℃. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0176] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0177] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0178] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0179] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 1:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 3%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0180] Embodiment 26

[0181] The total dosage of the agent was changed to 5%, and the addition amounts of other components and the operation were the same as in Example 25.

[0182] Embodiment 27

[0183] The total dosage of the agent was changed to 8%, and the addition amounts of other components and the operation were the same as in Example 25.

[0184] Examples 25 to 27 explored the effect of the dosage of the agent on the remediation efficiency of petroleum hydrocarbon contaminated soil when remediating petroleum hydrocarbon contaminated soil. The results are as follows: Fig. 9 When the total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) is added in an amount of 3%-8%, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 50%. When the amount is 5%-8%, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeds 80%.

[0185] Embodiment 28

[0186] 1) Extract aluminum from fly ash to prepare aluminum chloride.

[0187] Put fly ash into concentrated hydrochloric acid, and the volume ratio of fly ash mass to concentrated hydrochloric acid (g:ml) is 1:2. The concentration of concentrated hydrochloric acid is 36%. Heat the mixed solution at 250℃ for 4h to obtain aluminum acid liquid. Dilute the aluminum acid liquid with water, stir for 30min at 85℃, and then perform hot filtration. After hot filtration, stir the liquid at 115℃ for 15min, cool to room temperature, and obtain the first precipitated aluminum chloride white crystals for solid-liquid separation. Dry the obtained solid at 70℃ for 12h, and let the remaining filtrate stand at room temperature for 12h, and aluminum chloride precipitates for the second time. Dry the solid obtained from the second precipitation at 70℃ for 12h.

[0188] 2) Use steel slag to extract iron and prepare Fe3O4 at nanoscale.

[0189] Put the steel slag into dilute hydrochloric acid, the steel slag mass and dilute hydrochloric acid volume ratio (g:ml) is 1:4, the concentration of dilute hydrochloric acid is 10%, mix and stir for 12h, separate the solution into solid and liquid, and obtain an iron-containing filtrate. Add sodium hydroxide to the iron-containing filtrate, adjust the pH to 9-10, and obtain iron hydroxide precipitate. When the precipitate no longer continues to form, perform solid-liquid separation. Wash the precipitate with deionized water. After washing, the precipitate is pyrolyzed in an air atmosphere for 8h at a temperature of 600℃. Then take out the solid material and pyrolyze it in a hydrogen atmosphere for 4h at a temperature of 800℃. Use grinding equipment to grind the resulting product to obtain nano-scale Fe3O4.

[0190] 3) Synthesize a new metal-organic framework structure composite material PVA-Fe3O4@Al-MOF.

[0191] Aluminum chloride is dispersed in dimethylformamide, and the mass ratio of aluminum chloride to dimethylformamide volume ratio (g:L) is 0.267:1. Nano-sized Fe3O4 is added thereto, and the mass ratio of aluminum chloride to Fe3O4 (g:L) is 2.67:1. Ultrasonic treatment is performed for 30 minutes to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution. Trimellitic acid is taken, and the mass ratio of trimesic acid to aluminum chloride is 6.3:2.67, dissolved in dimethylformamide, and the mass ratio of trimesic acid to dimethylformamide volume ratio (g:L) is 0.63:1. Ultrasonic treatment is performed for 30 minutes to obtain a trimesic acid-dimethylformamide solution. The aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are placed in a reactor and heated in a hot environment of 120°C for 8 hours to obtain a solid-liquid mixed solution. The solid-liquid mixed solution was cooled to room temperature, and solid-liquid separation was performed to obtain Fe3O4@Al-MOF in a wet state. Fe3O4@Al-MOF was washed with dimethylformamide and dried in a hot environment at 60°C for 12 hours. Polyvinyl alcohol powder was dissolved in water to prepare a polyvinyl alcohol solution with a concentration of 5%, and allowed to stand to room temperature (25°C). Fe3O4@Al-MOF was added to the PVA solution, ensuring that the MOF material was completely immersed and stirred thoroughly for 30 minutes, and soaked for 5 days. The treated PVA-Fe3O4@Al-MOF was filtered out and rinsed alternately with water and ethanol. Subsequently, it was dried in a hot environment at 60°C for 12 hours.

[0192] 4) Use the prepared composite material PVA-Fe3O4@Al-MOF to catalyze sodium percarbonate to repair petroleum hydrocarbon contaminated soil.

[0193] Take the petroleum hydrocarbon contaminated soil and air dry it, remove stones, tree roots and other debris. Disperse sodium percarbonate in water, the mass ratio of sodium percarbonate to water is 1:7, and obtain solution A; disperse PVA-Fe3O4@Al-MOF in water, the mass ratio of PVA-Fe3O4@Al-MOF to water is 1:3, the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 3:1, add citric acid, the mass ratio of citric acid to PVA-Fe3O4@Al-MOF is 2:1, and obtain solution B. Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly. The total oxidizing agent (sodium percarbonate + PVA-Fe3O4@Al-MOF + citric acid) dosage is 1%. Then pour the sodium percarbonate solution into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes. Let it stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

[0194] Embodiment 29

[0195] The mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF was changed to 2:1, and the addition amounts of other components and the operations were the same as in Example 28.

[0196] Embodiment 30

[0197] The mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF was changed to 1:2, and the addition amounts of other components and the operations were the same as in Example 28.

[0198] Embodiment 31

[0199] The mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF was changed to 1:3, and the addition amounts of other components and the operations were the same as in Example 28.

[0200] In Example 28 to Example 31, the effects of the dosage of sodium percarbonate and PVA-Fe3O4@Al-MOF on the remediation efficiency of petroleum hydrocarbon contaminated soil were investigated. When the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF was 2:(1-4), the remediation efficiency of petroleum hydrocarbon contaminated soil exceeded 45%. When the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF was 1:2, the remediation efficiency of petroleum hydrocarbon contaminated soil exceeded 45%.

[0201] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention.

Claims

1. A method for preparing a novel metal-organic framework composite material based on fly ash and steel slag, characterized in that: The steps include: S1. Preparation of aluminum chloride using fly ash: The fly ash is added into concentrated hydrochloric acid, mixed and heated to obtain an aluminum acid solution, which is then diluted and filtered to obtain a filtrate, and the filtrate is cooled to room temperature to precipitate white aluminum chloride crystals; S2. Preparation of nano-Fe3O4 using steel slag: The steel slag is put into dilute hydrochloric acid, mixed and stirred for a period of time, and then solid-liquid separation is performed to obtain an iron-containing filtrate; sodium hydroxide is added to the iron-containing filtrate to obtain an iron hydroxide precipitate; the iron hydroxide precipitate is first pyrolyzed in an air environment, then pyrolyzed in a hydrogen atmosphere, and finally the product is ground to obtain nano-sized Fe3O4; S3. Synthesis of a novel metal-organic framework composite material PVA-Fe3O4@Al-MOF: Aluminum chloride is dispersed in dimethylformamide, and then nano-sized Fe3O4 is added to obtain an aluminum chloride-dimethylformamide-ferroferric oxide mixed solution; Dissolve trimesic acid in dimethylformamide to obtain a trimesic acid-dimethylformamide solution; A mixed solution of aluminum chloride-dimethylformamide-ferroferric oxide and a solution of trimesic acid-dimethylformamide were placed in a reactor, and after heating for a period of time, solid-liquid separation was performed to obtain Fe3O4@Al-MOF. Fe3O4@Al-MOF was added into an aqueous solution of polyvinyl alcohol, and after soaking for a period of time, the solution was filtered to obtain PVA-Fe3O4@Al-MOF.

2. The preparation method according to claim 1, characterized in that: In S1, the volume ratio of fly ash mass to concentrated hydrochloric acid is 1 g: (3-5) ml, and the mass percentage concentration range of concentrated hydrochloric acid is 36%-38%.

3. The preparation method according to claim 1, characterized in that: In S2, the volume ratio of steel slag to dilute hydrochloric acid is 1g:(6-10)ml, and the mass percentage concentration of dilute hydrochloric acid is 8%-12%; The temperature of pyrolysis of iron hydroxide precipitate in air environment is 700℃-800℃; The temperature of pyrolysis in a hydrogen atmosphere is 900°C-1000°C.

4. The preparation method according to claim 1, characterized in that: In S3, 1) In the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution, the mass ratio of aluminum chloride to dimethylformamide is (0.534-0.801) g:1 L, and the mass ratio of aluminum chloride to ferroferric oxide is (4.005-5.34):1; 2) In the trimesic acid-dimethylformamide solution, the mass ratio of trimesic acid to dimethylformamide is (0.315-0.63) g:1L; 3) After the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution are mixed, the mass ratio of trimesic acid to aluminum chloride is (3.15-4.725):2.

67.

5. The preparation method according to claim 1, characterized in that: The specific steps of S1 are as follows: S1-1, adding fly ash into concentrated hydrochloric acid, heating the mixed solution at 200°C-300°C for 4h-6h to obtain an aluminum acid solution; S1-2, dilute the aluminum acid solution with water, stir at 80°C-90°C for 30min-40min, then maintain the temperature and perform hot filtration under stirring; the volume of water added is three to four times the amount of concentrated hydrochloric acid in S1-1; S1-3, stirring the liquid obtained after hot filtration at 110°C-120°C for 15min-20min, cooling to room temperature, obtaining the first precipitation of aluminum chloride white crystals, and performing solid-liquid separation; the remaining filtrate was allowed to stand at room temperature for 12h, and aluminum chloride was precipitated as aluminum chloride white crystals for the second time; S1-4, drying the first and second precipitated aluminum chloride white crystals at 70°C-80°C for 12h-14h.

6. The preparation method according to claim 1, characterized in that: The specific steps of S2 are as follows: S2-1, adding steel slag into dilute hydrochloric acid, mixing and stirring for 12-14 hours, separating the solution into solid and liquid, and obtaining an iron-containing filtrate; S2-2, adding sodium hydroxide to the iron-containing filtrate, adjusting the pH to 9-10, obtaining iron hydroxide precipitate, and performing solid-liquid separation when the precipitate no longer continues to be generated; S2-3, washing the precipitate with deionized water, and then pyrolyzing the precipitate in an air atmosphere for 8h-10h; S2-4, then taking out the solid matter and pyrolyzing it in a hydrogen atmosphere for 4h-6h; S2-5. Grind the obtained product using a grinding device to obtain nano-sized Fe3O4.

7. The preparation method according to claim 1, characterized in that: The specific steps of S3 are as follows: S3-1, disperse aluminum chloride in dimethylformamide, add nano-sized Fe3O4, Ultrasonic treatment for 30 min to 60 min to obtain a mixed solution of aluminum chloride-dimethylformamide-ferroferric oxide; Dissolve trimesic acid in dimethylformamide and perform ultrasonic treatment for 30 min to 60 min to obtain a trimesic acid-dimethylformamide solution; S3-2, placing the aluminum chloride-dimethylformamide-ferroferric oxide mixed solution and the trimesic acid-dimethylformamide solution in a reaction kettle, and heating them in a hot environment of 120° C.-140° C. for 8 h-10 h to obtain a solid-liquid mixed solution; S3-3, cooling the solid-liquid mixed solution to room temperature, performing solid-liquid separation, and obtaining Fe3O4@Al-MOF in a wet state; S3-4, Fe3O4@Al-MOF was cleaned with dimethylformamide and dried in a hot environment of 60℃-70℃ for 12h; S3-5, dissolving polyvinyl alcohol powder in water to prepare a polyvinyl alcohol solution with a mass percentage concentration of 5%-6%, and letting it stand to room temperature; S3-6, adding Fe3O4@Al-MOF to the PVA solution, ensuring that the Fe3O4@Al-MOF material is completely immersed and fully stirred for 30min-60min, soaking for 5 to 6 days, and filtering to obtain PVA-Fe3O4@Al-MOF; Step S3-7, the PVA-Fe3O4@Al-MOF was rinsed alternately with water and ethanol, and then dried in a hot environment of 60°C-70°C for 12h.

8. A method for repairing petroleum hydrocarbon contaminated soil using a novel metal-organic framework structure composite material catalyzed by sodium percarbonate, characterized in that: The novel metal-organic framework structure composite material is prepared by the preparation method of claim 1, and the method for repairing petroleum hydrocarbon contaminated soil comprises the following steps: Step 1: Pre-treating petroleum hydrocarbon contaminated soil; Step 2: Preparation of repair agent using PVA-Fe3O4@Al-MOF Sodium percarbonate was dispersed in water to obtain solution A; PVA-Fe3O4@Al-MOF was dispersed in water and citric acid was added to obtain solution B; In solution A, the mass ratio of sodium percarbonate to water is 1:7; In solution B, the mass ratio of PVA-Fe3O4@Al-MOF to water was 1:3, and the mass ratio of citric acid to PVA-Fe3O4@Al-MOF was 2:1; Step 2: Pour solution B into the petroleum hydrocarbon contaminated soil and stir evenly, then pour solution A into the petroleum hydrocarbon contaminated soil and continue stirring for 5 minutes; In petroleum hydrocarbon contaminated soil, the dosage of sodium percarbonate, PVA-Fe3O4@Al-MOF, and citric acid is 3%-8%, and the mass ratio of sodium percarbonate to PVA-Fe3O4@Al-MOF is 2:(1-4); Step 3: Let the soil stand for 7 days and measure the concentration of petroleum hydrocarbons in the soil.

9. The method for remediating petroleum hydrocarbon contaminated soil according to claim 8, characterized in that: The pretreatment method for petroleum hydrocarbon contaminated soil is: air-dry the soil, remove stones and roots, and pass through a 2mm sieve.

Citation Information

Cited By

  • MOFs in-situ growth modified steel slag aggregate and preparation method of active carbon sequestration / intelligent self-repairing ultrathin wearing layer asphalt mixture

    CN121894957A